Implementation and Impact of Language Policy: The Case of Kyrgyz Students - Mambetaliev Askarbek; Мамбеталієв Аскарбек (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. Language policy is crucial to any society's cultural and political fabric, as it shapes how individuals and groups communicate, interact, and identify. Language policy has important implications for nation-building and the creation of national identity. Language policy can also significantly impact university students' sense of belonging. Overt and inclusive policies can provide opportunities for students to develop language skills and cultural competencies, enhancing their academic and professional opportunities. Covert and implicit policies can create barriers to interaction between different language groups, leading to social fragmentation, exclusion, and discrimination. Overt language policies are those that are openly acknowledged and implemented, while covert policies are those that are more subtle and may be hidden. Overt language policies that promote a single national language can unite diverse groups within a nation. However, these policies can also lead to the suppression of linguistic and cultural diversity within a nation, potentially undermining the cultural richness of that society. Covert language policies can also have significant impacts on identity and national unity. For example, language policies not openly acknowledged can lead to confusion or mistrust among different language groups. These policies can reinforce power imbalances between language groups, perpetuating existing inequalities. Considering these concepts, this study aimed to answer the following questions: 1. What LP has been implemented in Kyrgyzstan? 2. How has LP affected university students? Information on the language policy implemented in Kyrgyzstan was necessary to answer the first question, which involved examining laws, banknotes, newspaper titles, and dissertation catalogs. It was necessary to gather data on how the language policy has affected the students to answer the second question. In addition, in-depth interviews with LP experts helped clarify both questions. The collected information was analyzed using textual analysis and statistical methods. Data analysis showed that different models of language policy were implemented in Kyrgyzstan, including multilingualism, bilingualism, and monolingualism. Overt, covert, and vague LP were used to promote these models. These models and methods have formed segregated communities, language discrimination, and different linguistic identities within the same ethnic groups.

Резюме. Мовна політика має вирішальне значення для культурної та політичної структури будь-якого суспільства, оскільки вона формує спосіб спілкування, взаємодії та ідентифікації індивідів і груп. Мовна політика має важливі наслідки для націєтворення та формування національної ідентичності, також може суттєво впливати на почуття приналежності студентів університетів. Відкрита та інклюзивна мовна політика може надати студентам можливість розвивати свої мовні навички та культурні компетенції, розширюючи академічні та професійні можливості. Прихована і неявна політика може створювати бар'єри для взаємодії між різними мовними (етнолінгвістичними) групами, що призводить до соціальної фрагментації, виключення та дискримінації. Відкрита мовна політика – це та, що відкрито визнається і впроваджується, прихована політика – це та, що є більш витонченою і може бути частково або повністю прихованою. Відкрита мовна політика, яка підтримує єдину національну мову, може об'єднати різні групи всередині нації. Однак така політика також може призвести до придушення мовного та культурного розмаїття всередині нації, що потенційно підриває культурне багатство суспільства. Прихована мовна політика також може мати значний вплив на ідентичність та національну єдність. Наприклад, мовна політика, яка не визнається відкрито, може призвести до плутанини або недовіри між різними мовними групами. Така політика може посилити дисбаланс влади між мовними групами, увічнюючи існуючу нерівність. Беручи до уваги ці концепції, це дослідження мало на меті дати відповіді на наступні питання: 1. Яка мовна політика була реалізована в Киргизстані? 2. Як ця політика вплинула на студентів університетів? Для відповіді на перше питання була необхідна інформація про мовну політику, що реалізується в Киргизстані, для чого було вивчено закони, банкноти, назви газет і каталоги дисертацій. Для відповіді на друге питання необхідно було зібрати дані про те, як мовна політика вплинула на студентів. Крім того, глибинні інтерв'ю з експертами з мовної політики допомогли прояснити обидва питання. Зібрану інформацію було проаналізовано за допомогою текстового аналізу та статистичних методів. Аналіз даних показав, що в Киргизстані реалізуються різні моделі мовної політики, включаючи багатомовність, двомовність і одномовність. Для просування цих моделей використовувалися відкриті, приховані та нечіткі приклади мовної політики. Ці моделі та методи сформували сегреговані спільноти, мовну дискримінацію та різні мовні ідентичності в межах одних і тих самих етнічних груп.

A nyelvpolitika minden társadalom kulturális és politikai szerkezetében alapvető fontosságú, mivel meghatározza az egyének és csoportok kommunikációját, kölcsönhatásait és azonosítását. A nyelvpolitika fontos hatással van a nemzetépítésre és a nemzeti identitás kialakítására. A nyelvpolitika jelentősen befolyásolhatja az egyetemi hallgatók hovatartozás-érzését is. A nyílt és befogadó politikák lehetőséget biztosíthatnak a hallgatók számára a nyelvi készségek és a kulturális kompetenciák fejlesztésére, javítva ezzel tanulmányi és szakmai lehetőségeiket. A rejtett és hallgatólagos politikák akadályokat állíthatnak a különböző nyelvi csoportok közötti interakció elé, ami társadalmi széttagoltsághoz, kirekesztéshez és diszkriminációhoz vezethet. A nyílt nyelvpolitikák azok, amelyeket nyíltan felvállalnak és végrehajtanak, míg a rejtett politikák azok, amelyek finomabbak és rejtettebbek lehetnek. Az egyetlen nemzeti nyelvet támogató nyílt nyelvpolitikák egyesíthetik a nemzeten belüli különböző csoportokat. Ezek a politikák azonban a nemzeten belüli nyelvi és kulturális sokszínűség elfojtásához is vezethetnek, ami alááshatja az adott társadalom kulturális gazdagságát. A burkolt nyelvpolitikák szintén jelentős hatással lehetnek az identitásra és a nemzeti egységre. Például a nem nyíltan elismert nyelvpolitikák zavart vagy bizalmatlanságot okozhatnak a különböző nyelvi csoportok között. Ezek a politikák erősíthetik a nyelvi csoportok közötti hatalmi egyenlőtlenségeket, és állandósíthatják a meglévő egyenlőtlenségeket. Ezeket a fogalmakat figyelembe véve ez a tanulmány a következő kérdésekre kereste a választ: 1. Milyen nyelvpolitikát hajtottak végre Kirgizisztánban? 2. Hogyan hatott a nyelvpolitika az egyetemi hallgatókra? Az első kérdés megválaszolásához a Kirgizisztánban megvalósított nyelvpolitikára vonatkozó információkra volt szükség, amely magában foglalta a törvények, bankjegyek, újságcímek és disszertációs katalógusok vizsgálatát. A második kérdés megválaszolásához adatokat kellett gyűjteni arról, hogy a nyelvpolitika hogyan hatott a diákokra. Emellett a nyelvtanulási szakértőkkel készített mélyinterjúk segítettek mindkét kérdés tisztázásában. Az összegyűjtött információkat szövegelemzéssel és statisztikai módszerekkel elemeztük. Az adatelemzés kimutatta, hogy Kirgizisztánban a nyelvpolitika különböző modelljeit valósították meg, beleértve a többnyelvűséget, a kétnyelvűséget és az egynyelvűséget. Nyílt, rejtett és homályos nyelvpolitikát használtak e modellek népszerűsítésére. Ezek a modellek és módszerek szegregált közösségeket, nyelvi diszkriminációt és különböző nyelvi identitásokat alakítottak ki ugyanazon etnikai csoportokon belül.
A nyelvpolitika megvalósítása és hatása: A kirgiz diákok esete
Реалізація та вплив мовної політики: приклад киргизьких студентів університетів
https://aab-philologica.kmf.uz.ua/aabp
Keywords: Overt and covert language policies; impact of language policy on national identity; top-down and bottom-up aspects; lingustic behavior; macro and micro level policies